Global research trends related to coronavirus disease 2019 and the aged: a bibliometric analysis - Carvalho, Ana Raquel Batista de; Sousa Neto, Antonio Rosa de; Silva, Márcia Daiane Ferreira da; Freitas, Daniela Reis Joaquim de; Moura, Maria Eliete Batista (São Paulo medical journal, 2024)
A bibliometric analysis covering only the production of original studies or considering world production until 2022 has yet to be conducted. The creation and advancement of vaccines have also influenced research priorities, demonstrating the need for a new approach to this subject. To analyze worldwide scientific production related to coronavirus disease 2019 (COVID-19) and the aged and to describe what has already been produced. Bibliometric analysis with a quantitative approach. The search terms "COVID-19," "SARS-CoV-2," "Aged," and "Elderly" were used to retrieve articles from the Web of Science database. A total of 684 articles were included in the analysis. Data were imported into RStudio Desktop Software and linked to R Software. The Bibliometrix R package and VOSviewer software were used for analysis. Most articles were published in 2020. These were produced by 4,937 authors and published in 379 journals. The keyword most used by the authors was "COVID-19." Publications from 77 countries were obtained. China had the highest article production ranking, and Spain collaborated the most. The articles addressed the implications of the pandemic on the aged, the relationship between vaccination in the aged, and the implications for the disease itself. Further research should be conducted, mainly concerning vaccines and vaccination of the aged, owing to the need for and importance of immunization in this risk group, including assessing the long-term effects of vaccines.